A Home Education Service to Increase Knowledge of Treatment Options and Improve Attitudes to Living Donor Kidney Transplantation. (March 2023) - Hobson, Orla; Lumsdaine, Jen; Sherif, Ahmed; Oniscu, Gabriel C.
Introduction: Lack of knowledge about living donor kidney transplant and difficulties in approaching potential donors constitute barriers for many patients and may contribute to inequality of access.Project Aims: Renal Education and Choices at Home was a UK single-centre pilot of home education; an initiative aiming to overcome barriers by increasing knowledge among patients and support networks and by facilitating living donation discussion in the patient's home.Design: This was a pre-post comparison of knowledge, attitude, and ability to communicate about transplant. Pre-visit knowledge about treatment options and attitudes towards transplant were measured using a validated questionnaire, repeated 4–6 weeks post-visit, to assess the session's impact, along with an evaluation survey, to determine how patients perceived the session.Results: From November 2018 to February 2020, a nurse specialist delivered living donor transplant education sessions in the homes of 86 patients, attended by 141 additional invitees. Home visits led to a significant improvement in knowledge about renal therapies, including living donor transplantation. The evaluation of the home visits by patients and invitees was overwhelmingly positive. Of the 86 patients visited, 46 (53%) had at least one potential donor initiating the assessment process following the visit. Overall, 78 potential donors initiated the assessment process.Conclusion: Home education contributed to addressing recognised barriers, in a way that was well received by patients and was novel in our health system. Home education may be particularly beneficial for patients affected by known barriers to living donor transplantation such as socio-economic deprivation.